Reproductive Health Training Program to Strengthen Private Midwifery Practice in The Context of Covid-19 Pandemic in Indonesia–an Emergency Response - Nohan Arum Romadlona; Intan Wahyu Cahyani (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2023)
The COVID-19 pandemic has had impact on reproductive health services. Based on data from Basic Health Research in 2018, more than 50% reproductive health services provided by midwives in private midwifery practices. As private midwifery practice was first choice for women to fulfil essential need in reproductive health, it is important to strengthen its quality. Cross-sector collaboration led by Knowledge Hub for Reproductive Health Indonesia has carried out training on reproductive health services during COVID-19 pandemic. The aim of the training is building capacity to offer high-quality reproductive health services while at the same time minimizing the risk of COVID-19 transmission.